Increasing Environmental Awareness of Entrepreneurs and Digital-Based Marketing Mechanisms for MSME Products - SELAMET, I Ketut; LAKSMI, Putu Ayu Sita; SAPUTRA, Komang Adi Kurniawan; PUTRA, I Komang (Community Services: Sustainability Development, 2025)
Environmental awareness among MSMEs in Dauh Puri Kangin Village is crucial for promoting sustainability and improving public health. Key aspects include 1) Implementing environmental business ethics to minimize production impacts and enhance sustainability; 2) Raising MSMEs' understanding and awareness of waste management; and 3) Government support to facilitate waste management, including improving IPAL facility operations. In addition to environmental concerns, MSMEs face challenges such as limited business capital, licensing issues, poor financial management, lack of product innovation, and difficulties in business development. Addressing these obstacles is essential for their growth. Digital marketing offers significant opportunities for MSMEs to expand their market reach. Effective strategies include: 1) Creating mobile-friendly websites to showcase products, design promotional campaigns, and provide seamless customer experiences; 2) Utilizing social media platforms for promotion, including forming dedicated customer groups on WhatsApp and Line to share product catalogs; 3) Collaborating with marketplaces like Shopee and Tokopedia to enhance payment security and customer trust; 4) Implementing email marketing campaigns to engage with potential customers; and 5) Providing responsive customer service through digital channels such as email, social media, and online chat platforms. Key principles of successful digital marketing involve understanding the target audience, selecting appropriate digital platforms, and analyzing marketing data to measure performance. By adopting these strategies, MSMEs in Dauh Puri Kangin Village can achieve sustainable growth, enhance competitiveness, and contribute positively to environmental and economic development.